THE RELATIONSHIP BETWEEN WORK LIFE BALANCE AND PSYCHOLOGICAL WELL BEING AMONG FEMALE SPECIAL NEEDS SCHOOL TEACHERS - Giarto, Nicky Angelica; Sarajar, Dewita Karema (Program Studi Bimbingan dan Konseling Universitas Tunas Pembangunan Surakarta, 2024)
The challenges faced by Special Needs School (SLB) teachers are more complex compared to regular school teachers. The complexity of the conditions of children with special needs requires educators to regulate more extensively to condition Special Needs Children (ABK) in a humane manner. The background of this research highlights the complexity of the dual roles undertaken by female SLB teachers, who also serve as mothers and wives. This study aims to determine the relationship between work-life balance and psychological well-being among female SLB teachers in Solo Raya. This study involves 110 female SLB teachers in Solo Raya as research subjects. The research method used in this study is quantitative correlational research. The research instruments for this research are work life balance by Fisher (2009) and Psychological well being by Ryff (1995). The results of the study show a significant positive correlation with a result of r = 0.352 and a significance value of 0.000 (p<0.05), which means that the higher the work-life balance, the higher the psychological well-being. The work-life balance variable contributes effectively by 12.3% to psychological well-being. Meanwhile, 87.7% of the psychological well-being variable is still influenced by other factors